Pengaruh Financial Distress, Profitabilitas, dan Opini Audit terhadap Audit Delay dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2022 - Yunita Ariyani; Rahmaita (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to determine the effect of financial distress, profitability, and audit opinion on audit delay with company size as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. This research uses a quantitative descriptive approach. The data used are secondary data and annual reports of energy sector companies listed on the IDX. The sampling technique in this study used non-probability sampling and the method used in this research is purposive sampling method. The samples in this study were 12 companies in the energy sector. The research results showed that partially financial distress and profitability had no significant effect on audit delay. Audit Opinion has a significant effect on audit delay. Company size is unable to moderate the influence of financial distress and profitability on audit delay. Meanwhile, company size is able to moderate the influence of audit opinion on audit delay.